Transportation of Cull Sows—Deterioration of Clinical Condition From Departure and Until Arrival at the Slaughter Plant - Thodberg, Karen; Fogsgaard, Katrine Kop; Herskin, Mette S. (Frontiers in Veterinary Science, 2019)
Cull sows may be more vulnerable towards transportation compared to other swine categories, but until now, transportation of sows has received very little scientific attention. We aimed, based on cull sow transportation from commercial Danish herds to slaughter plant, to investigate whether the clinical condition of the sows changed during transportation, and to initiate identification of potential risk factors for such deterioration. This observational study included 522 sows in 47 batches from 12 herds, varying according to transportation time from herd to slaughter plant. Standardized clinical examinations were conducted on-farm and at the slaughter plant. In addition data on transportation duration, number and duration of stops, temperature during driving, and during waiting before unloading were collected. The sows’ median parity was five (range 1-11) and close to 40% were lactating at the day of transportation. The mean duration of transportation was 232 ± 113 min, and the mean temperature in the trucks was 14.1 ± 5.3°C. Half of the clinical variables recorded before and after transportation changed significantly. Among these were injuries (e.g. superficial skin lesion, totally, P < 0.000; front, P < 0.001; wounds, P < 0.001; gait score, P < 0.001), and measures possibly related to heat stress (e.g. skin elasticity, P < 0.001). Three sows arrived in a condition as legally unfit for transport. The deterioration of the sows’ condition was mainly related to transportation factors, such as temperature and duration – often in interaction – as well as duration of stops during the journey and while waiting before unloading. The changes in clinical condition were less dependent on the pre-transportation clinical condition of the sows. The results show that the clinical condition of the cull sows deteriorated on the way from herd to slaughter plant, thereby adding data to the debate on fitness for transport of cull sows. The main risk factors for the deterioration were not related to characteristics of the sows, but of the involved journeys. Future studies should focus on identifying and distinguishing between risk factors in order develop procedures that allow transportation of cull sows to slaughter without jeopardizing their welfare.